Feeding Preference of Cutlassfish (Trichiurus lepturus Linnaeus) in Coastal Waters of Gunungkidul, Yogyakarta - Paramita, Desak Putu Raka; Trijoko, Trijoko (Journal of Biology and Life Science, 2021)
Research on cutlassfish’s diet has been carried out in several areas, but similar research does not exist or still rarely found in Gunungkidul. The aim of this study is to determine the overall composition of the cutlassfish's food, the most dominant type of food and cutlassfish's growth pattern. Methods including random sampling in the field, measurement of length and weight and identification of food types using stomach analysis method and proximate analysis on both cutlassfish’s muscle and diet. The results of the study then analyzed using the formula by Walpole (1992), length-weight relationship formula according to Le Cren (1951) followed by determining the value of b with the t-test at confidence interval of 96% and condition factor. Food composition and preferences were calculated using numerical and volumetric methods to find the IP (Index of Preponderance) and IRI (Index Relative Importance) values. Composition based on types of food is dominated by fish at 89% with Engraulidae as the main group with total percentage of IP 45.58 and IRI 76.47, respectively. Proximate analysis values indicate low levels of protein (with highest value of 23.82%) and high-moisture content (with highest value of 71.98%) caused by cold temperatures during storage. The regression showed that cutlassfish have an allometric positive growth pattern. The results revealed that the food is sufficient for the growth of cutlassfish (Trichiurus lepturus).